Improving Forecasting Accuracy For Time Series Data Using Fuzzy Techniques And Wavelet Transform - Hobaykan A, Alenezy Abdullah (2025)
This study focuses on improving the accuracy of stock market forecasting for the Saudi Arabia stock exchange (Tadawul) by employing advanced modeling techniques and adaptive learning approaches. The study utilizes the maximum overlapping discrete wavelet transform (MODWT) in conjunction with various mathematical functions to analyze daily stock price indices data from October 2011 to December 2019.